The potential of private institutional investors for the financing of transport infrastructure - Rajiv Sharma (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2013)
It is widely held that large institutional investors such as pension funds and sovereign wealth funds with long term liabilities and a low risk appetite are ideally suited to invest in transportation infrastructure assets. Despite the theoretical ideal match between a large source of capital and an asset class in need of investment, the uptake of institutional investors has been slow. This has been due to bad experiences with early investments and the uncertainty associated with investing in some transportation infrastructure assets...
Keywords: 330; Verkehrsinvestition; Institutioneller Investor